Effect of MgO Buffer Layer on The Quality of ZnO Films Grown on C-Sapphire by Plasma-assisted MBE Method - Agus Setiawan; Takafumi Yao (Jurnal ILMU DASAR, 2011)
We have investigated the role of low temperature (LT)-MgO buffer layer on the quality of ZnO films grown on c-sapphirebyplasma-assistedmolecularbeamepitaxy(P-MBE)method. EffectofMgObufferthicknessand its annealing were evaluated. We found that surface morphology and crystalline quality of the ZnO layers were improved by controlling of the buffer layers. There is no improvement in morphology and crystalline quality of the ZnO layers if the buffer thickness is less than the critical thickness. The critical thickness is determined to be 1.5 nm. Furthermore, surface, structural, optical, and electrical qualities of the ZnO layers were improved by annealing MgO buffer at high temperature. Dislocation density of the ZnO layer was reduced from 5.3 x109 cm-2 to 1.9 x109 cm-2 by annealing the MgO buffer layer. The results indicate that we can engineer defect in highly mismatched heteroepitaxial using buffer layer.